Multiple discrete endogenous variables in weakly-separable triangular models - Sung Jae Jun; Joris Pinkse; Haiqing Xu; Neşe Yıldız (Econometrics, 2016)
We consider a model in which an outcome depends on two discrete treatment variables, where one treatment is given before the other. We formulate a three-equation triangular system with weak separability conditions. Without assuming assignment is random, we establish the identification of an average structural function using two-step matching. We also consider decomposing the effect of the first treatment into direct and indirect effects, which are shown to be identified by the proposed methodology. We allow for both of the treatment variables to be non-binary and do not appeal to an identification-at-infinity argument.
Keywords: C01; C14; C31; 330; nonparametric identification; discrete endogenous regressors; triangular models